2019
DOI: 10.1186/s12862-019-1543-8
|View full text |Cite
|
Sign up to set email alerts
|

Human-specific mutations in VMAT1 confer functional changes and multi-directional evolution in the regulation of monoamine circuits

Abstract: BackgroundNeurochemicals like serotonin and dopamine play crucial roles in human cognitive and emotional functions. Vesicular monoamine transporter 1 (VMAT1) transports monoamine neurotransmitters, and its variant (136Thr) is associated with various psychopathological symptoms and reduced monoamine uptake relative to 136Ile. We previously showed that two human-specific amino acid substitutions (Glu130Gly and Asn136Thr/Ile) of VMAT1 were subject to positive natural selection. However, the potential functional a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 57 publications
1
8
0
Order By: Relevance
“…These phenotype changes (i.e., a pattern in which Vmat1 Thr exhibits a similar phenotype while Vmat1 Ile differs compared to Vmat1 WT ) are in line with the in silico prediction of differentiated transport function for the mVMAT1 133Ile (Table 1, Fig. 1b) likewise in the hVMAT1 136Ile 16,17 and previous studies demonstrating altered fear/anxiety responses and psychopathological effects of the variant 16,20 .…”
Section: Fig 3csupporting
confidence: 88%
See 3 more Smart Citations
“…These phenotype changes (i.e., a pattern in which Vmat1 Thr exhibits a similar phenotype while Vmat1 Ile differs compared to Vmat1 WT ) are in line with the in silico prediction of differentiated transport function for the mVMAT1 133Ile (Table 1, Fig. 1b) likewise in the hVMAT1 136Ile 16,17 and previous studies demonstrating altered fear/anxiety responses and psychopathological effects of the variant 16,20 .…”
Section: Fig 3csupporting
confidence: 88%
“…Compared to Vmat1 Ile (Vmat1 Thr/Ile and Vmat1 Ile/Ile ) mice, both wildtype and Vmat1 Thr/Thr mice showed similar behavioral phenotypes and have higher levels of anxiety in both solitary (LD, EP, and OF) and social (SI and CSI) environment. This is expected from the molecular evidence that 136Asn and 136Thr are comparable in the level of monoamine uptake, which is lower than that of 136Ile (15). It is noteworthy that the genotypic effect was not observed for fear response of mice (Supplementary Fig.…”
Section: Phenotypic Changes In Mice Caused By the Humanized Vmat1mentioning
confidence: 64%
See 2 more Smart Citations
“…Our previous study showed that a new mutation at the 136th amino acid (136Ile) of VMAT1 has emerged relatively recently in the course of human evolution and that the human-specific polymorphism Thr136Ile has likely been maintained by balancing selection within non-African populations ( Sato and Kawata, 2018 ). Fluorometric assays additionally demonstrated that these human-specific residues enhance monoamine neurotransmitter uptake, suggesting the tendency of lower monoamine uptake in early hominids ( Sato et al., 2019 ). The 136Thr, the dominant variant across populations, is known to be marginally associated with psychiatric diseases, such as bipolar disorder, depression, and anxiety, as well as with neuroticism, a personality trait conferring a greater risk of psychiatric disease ( Lohoff et al., 2006 , 2008a ; Vaht et al., 2016 ).…”
Section: Introductionmentioning
confidence: 99%